Producing a Spatial Signature Map of Solar Energy services Sites, in Al-Qunfudah Governorate in the Emirate of Makkah Al-Mukarramah Region KSA, Using Geographic Information System (GIS) - Alshehabi, خيرية علي حسن (Journal of King Abdulaziz University: Environmental Design Sciences, 2026)
The present study targets for producing a spatial signature map of solar energy services sites, in Al-Qunfudah Governorate in the western part of the Kingdom of Saudi Arabia, in the Emirate of Makkah Al-Mukarramah Region. The study used the descriptive analytical method, and techniques including the comprehensive analytical Henrik hierarchical, Geographic Information Systems (GIS) for assessing similarities that include the climatic, geographic and environmental factors of the East, determining the locations and determining the network of solar power stations for electric power in Al-Qunfudah Governorate. The results reached in the present study indicated that the general elimination of the values of the total general radiation reaching the surface of the earth in Al-Qunfudah Governorate from 1984 to 2022 has gradually decreased at the annual rate. The present study revealed that many factors control the ideal sites of solar power stations; the most important is the degree of direct exposure to solar radiation, the earth's surface slope where it degrades in the governorate, from east to west at the Red Sea coast, the elevation of the earth's surface and the direction of the slope of the earth's surface. The rest of the factors are of low impact. It turns out that what we want to think about is 2.72% of the total reduction of the main sites of power stations where the neighborhood area is 140.1374 square kilometers and is capable of generating a larger amount of solar energy, especially in the center of Thulatha Al-Kharm, and the center of Sabt Al-Tijara, which is located east of Al-Qunfudah Governorate. The present study recommends the specialists work hand in hand with the authority of the governorate in making plans for establishing new energy sources in the governorate. Establishment of solar power generation services is of the most economic importance for road and the electricity networks in the south of Al-Qunfudah Governorate. The authority needs to choose many large places in other gathering sites to establish solar power generation services. Spreading awareness in the local community based on the use of home solar energy is of real importance as well. It is here to encourage the owners of agricultural lands to adopt using solar energy.